Disrupting the Comfort Zone Rafael Bonachela Dance Company reviewed - Jennings, Luke (Dance Books Ltd., Alton,Hampshire (UK), 2008)
The conceptual point of departure was a quartered "map", one might find the four seasons, the four elements, the four ages of man and other quadratic notions. PALABRAS CLAVE: Square Map of Q4, Marius de Vries, Rafael Bonachela, Alan Macdonald, Meadham Kirchhoff, Guy Hoare.